Clinicopathological characteristics of gastric cancer with carbohydrate antigen 19‐9 expression occurring in elderly individuals: An autopsy study. Issue 2 (23rd December 2019) - Wang, Tan; Matsuda, Yoko; Nonaka, Keisuke; Kakizaki, Mototsune; Ishiwata, Toshiyuki; Kanazawa, Nobuo; Uegaki, Satoko; Muramatsu, Masaaki; Sawabe, Motoji; Mori, Seijiro; Tanaka, Masashi; Kitagawa, Masanobu; et al.
Abstract : The clinicopathological significance of carbohydrate antigen 19‐9 (CA19‐9) in gastric cancer (GC) remains obscure. Therefore, the current study aimed to clarify the clinicopathological value of CA19‐9 in GC utilizing autopsy cases. We examined the expression of CA19‐9 and mucin core proteins in GC immunohistochemically, and analyzed serum CA19‐9 levels and clinicopathological variables or complications. We also investigated whether fucosyltransferases 2 and 3 (FUT2/3) allelic variants influence CA19‐9 expression in GC. Compared to GC cases with negative CA19‐9 expression (tCA19‐9‐N), those with positive CA19‐9 expression (tCA19‐9‐P) demonstrated significant differences in characteristic features such as lymph node and distant organ metastases, lymphatic and venous permeation, and higher Tumor, Node, Metastasis (TNM) stages. Moreover, compared to GC cases with low serum CA19‐9 levels (sCA19‐9‐L), those with high serum CA19‐9 levels (sCA19‐9‐H) were related to venous permeation, higher proportion of lymph node and distant organ metastases, and higher TNM stages. Both tCA19‐9‐P GC and sCA19‐9‐H GC cases were significantly associated with coagulation abnormalities. sCA19‐9‐H GC cases correlated significantly with MUC1 and MUC5AC expression. FUT2/3 genotypes were not associated with CA19‐9 expression in GC. These results suggest that CA19‐9 can predict the risk of lymph node and distant metastases as well as of coagulation abnormalities.